Differences in the morphological body condition index of sea turtles between species and size classes. (11th November 2022) - Nishizawa, Hideaki; Joseph, Juanita
Abstract: The body condition of animals is an important indicator of their habitats and the effects of anthropogenic activities and pollution. Body condition indices calculated from morphometric measurements have been widely employed as they are easy to use and inexpensive. In sea turtles, Fulton's condition index, calculated as the bodyweight divided by the cube of straight carapace length (SCL), has been commonly used and it has been proposed that an index of ≥1.2 indicates a good body condition. However, comparing Fulton's condition index between different species and size classes is problematic as it does not consider the mass-length relationship. In this study, we conducted a meta-analysis to evaluate the differences between sea turtles. A literature review indicated that most studies reported the SCL-based Fulton's condition index for green turtles ( Chelonia mydas ), followed by loggerhead turtles ( Caretta caretta ) and hawksbill turtles ( Eretmochelys imbricata ). Therefore, we compared the values reported for healthy turtles of these three species. Meta-analysis supported the adequacy of 1.2 as a threshold in juvenile and adult green turtles and large juvenile and adult loggerhead turtles. High Fulton's condition index values were found for hatchlings and post-hatchlings of all three species and small loggerhead turtle juveniles. Low Fulton's condition index values were found for hawksbill turtles, particularly small juveniles. The differences in the Fulton's condition index between species and size classes indicated that it should be used carefully as a threshold for health condition evaluation.